2015
DOI: 10.1186/s12711-015-0146-0
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide association study of reproductive traits in Nellore heifers using Bayesian inference

Abstract: BackgroundAn important goal of Zebu breeding programs is to improve reproductive performance. A major problem faced with the genetic improvement of reproductive traits is that recording the time for an animal to reach sexual maturity is costly. Another issue is that accurate estimates of breeding values are obtained only a long time after the young bulls have gone through selection. An alternative to overcome these problems is to use traits that are indicators of the reproductive efficiency of the herd and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 34 publications
3
31
0
1
Order By: Relevance
“…Costa et al [10] also detected genes related to neural development that were associated with reproductive traits. Neurulation is an important and one of the first events of embryogenesis [64].…”
Section: Resultsmentioning
confidence: 99%
“…Costa et al [10] also detected genes related to neural development that were associated with reproductive traits. Neurulation is an important and one of the first events of embryogenesis [64].…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that genes related to ADG and SC could also be related to AFC. In fact, at least one single nucleotide polymorphism (SNP) within the region between 78.85 and 79.85 Mb on chromosome 10, and one SNP within the region between 23.4 and 33.85 Mb on chromosome 14 have been reported to affect both SC and AFC in Nellore cattle [34, 35]. …”
Section: Discussionmentioning
confidence: 99%
“…Cánovas et al (2014) analyzed eight tissues of pre-and post-pubertal Brangus heifers by RNA-Seq and found that hypothalamus samples had the greatest increase in the puberty regulatory genes as compared with the other analyzed tissues (pituitary gland, uterus, endometrium, ovary, liver, muscle and adipose tissue). In addition, several studies with Nelore heifers have shown that single nucleotide polymorphisms provide relevant information to help elucidate which genes affect puberty onset (Costa et al, 2015;Regatieri et al, 2017).…”
Section: Figurementioning
confidence: 99%